Effect of water and salinity on soil behaviour under lightning. Issue 1 (March 2016) - Rao, Pingping; Chen, Qingsheng; Nimbalkar, Sanjay; Liu, Yang
Abstract : The east coast of China, in particular Shanghai, is frequently exposed to lightning, and the resulting annual loss approaches US30 million. All kinds of protection devices transfer the lightning current and the energy into the ground. In this study, the characteristics of the typical soft soil in Shanghai with different values of water content and salinity under the action of lightning shock have been analysed by an impulse current generator and a self-designed test equipment. The test results show that the current waveform from the impact of lightning in soils has a steep rise and a slow fall. At the same lightning intensity, higher water content or salinity leads to ( a ) shorter peak time, ( b ) larger peak current waveform, ( c ) quicker release speed and ( d ) larger lightning impulse response. The test results are valuable in guiding the design and the reformation of lightning protection and grounding systems.